Surgical correction and postoperative period management of a patient with the giant left atrium: case report - Yakov Maul; Aidyn Kuanyshbek; Ivan Vakhrushev; Tatyana Li (National Scientific Medical Center, 2022)
This case report describes the history of a 62-year-old man with symptoms of severe heart failure caused by critical mitral valve (MV)  stenosis with extremely enlarged left atrium (LA) and chronic rheumatic heart disease. The patient has had MV replacement, aortic valve (AoV) replacement, tricuspid valve (TV) plastic surgery, left atrial thrombectomy, reduction, and resection of the LA. The operation was performed by median sternotomy, in condition of artificial blood circulation with aortic cannulation, separate cannulation of Cava veins and hypothermia up to 29 C. Selective antegrade cold blood cardioplegia was used for the myocardium protection. Revision of the MV was performed via the right atrium. Findings: the valves deformed by severe fibrosis, thickened subvalvular structures. Also, there was a massive thrombosis of the LA cavity. A thrombectomy was performed, total amount of evacuated thrombotic masses - 350 ml. Considering the circumstances of atriomegalia, was decided to provide reduction of the LA. MV replacement with mechanical prosthesis SJM MastersSeries # 31, aortic valve replacement with prosthesis SJM MastersSeries #25, and Suture commissuroannuloplasty were performed. We believe that our surgical tactics has effectively reduced the size of the LA, together with the correction of valvular malformation, can significantly improve the patient's life quality.